Changes in Calciotropic Hormones and Bone Markers During Pregnancy in Response to a Nutrition + Exercise Intervention in the Be Healthy in Pregnancy RCT (P11-023-19). (13th June 2019) - Perreault, Maude; Moore, Caroline; Fusch, Gerhard; Mottola, Michelle; Atkinson, Stephanie
Abstract: Objectives: Maternal bone health can be compromised in pregnancy if diet and exercise are inadequate. Our objective was to determine the changes of calciotropic hormones and bone biomarkers in response to a maternal high-dairy diet plus exercise intervention compared to usual care from early to late pregnancy. Methods: As part of the Be Healthy in Pregnancy RCT (Southern Ontario, Canada) (NCT01689961), healthy pregnant women (≤ 17 wk gestation) were randomized to the control or treatment group (Nutrition: 25% protein energy with ∼50% from dairy and Exercise plan: 10, 000 daily steps) for the duration of pregnancy. Calcium and vitamin D intakes were analyzed from 3-day diet and supplement records (Nutritionist Pro). Fasted serum was analyzed for 25(OH)D2 and D3 and 1, 25(OH)2 D by LC-MS/MS (Waters Corp.); procollagen type I N-terminal propeptide (PINP, Cloud Clone Corp., TX, USA) and insulin growth factor-1 (IGF-1, R&D Systems, MN, USA) by ELISA) at 12–17 and 36–38 wk gestation. T-tests were used to compare groups at baseline. Two-way ANOVA were performed to assess time and treatment effect. Results: In 118 women (86% of European descent, mean (range) pre-pregnancy BMI 24.9 kg/m2 (17.9 – 39.6 kg/m2)), baseline median (Q1, Q3) vitamin D and calcium intakes (585 IU/d (453, 823) and 1192 mg/d (979, 1512)) and bone biomarkers were similar between control and treatment groups. Baseline 25(OH)D was 79.6 nmol/L (66.1, 97.7), 1, 25(OH)2 D was 71.5 pmol/L (62.3, 89.8), PINP was 57.0 ng/mL (37.4, 74.2) and IGF-1 was 178.0 ng/mL (132.0, 212.0). At the end of pregnancy, concentrations of 25(OH)D, 1, 25(OH)2 D and IGF-1 increased significantly ( P  < 0.001) by 19%, 34% and 82%, respectively, compared to early pregnancy. PINP remained unchanged and no treatment or interaction effects were observed. Calcium intake was higher in treatment vs control group in late pregnancy (1678 (1285, 2036) vs 1251 (951, 1565) mg/d, P  < 0.005), but not vitamin D intake. Conclusions: Serum concentrations of all biochemical measures except the bone formation biomarker PINP rose from early to late pregnancy. A high-dairy diet and exercise regimen providing higher calcium intakes did not modulate the changes in bone status induced by pregnancy. Funding Sources: CIHR-Vanier and CCHCSP; Dairy Farmers of Canada, CIHR and DFC/AAFC Dairy Research Cluster; in-kind by GayLea Foods & Ultima Foods.